2009
DOI: 10.4067/s0717-92002009000100004
|View full text |Cite
|
Sign up to set email alerts
|

Vegetative propagation of patagonian cypress, a vulnerable species from the subantarctic forest of South America

Abstract: SUMMARYIncreasing risks of loosing forest genetic resources and the need for a sustainable quality wood supply make focusing research efforts on undomesticated tree species necessary. The study of their genetic variation in vegetative propagation ability and the development of practical methodologies to obtain genetic copies are essential tools for conservation and breeding programs. patagonian cypress Austrocedrus chilensis is a vulnerable conifer native to the subantarctic forest of South America, with high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
0
5
0
5
Order By: Relevance
“…In the present study, no significant differences were found in the provenance of the scions in relation to the survival of the grafts, since they resulted in being statistically similar (Table 6). In another study using scions from four different provenances in the Argentine Patagonia, the provenance did not affect the survival of grafts of Austrocedrus chilensis (D. Don) [46]. However, the provenance of the scions was found to influence the survival of Pinus patula grafts, in a study within which scions were collected from two different provenances in the state of Mexico [12].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, no significant differences were found in the provenance of the scions in relation to the survival of the grafts, since they resulted in being statistically similar (Table 6). In another study using scions from four different provenances in the Argentine Patagonia, the provenance did not affect the survival of grafts of Austrocedrus chilensis (D. Don) [46]. However, the provenance of the scions was found to influence the survival of Pinus patula grafts, in a study within which scions were collected from two different provenances in the state of Mexico [12].…”
Section: Discussionmentioning
confidence: 99%
“…Ello ha hecho necesario enfocar las investigaciones a aquellas especies que cumplen otras funciones como, por ejemplo, el soporte de ecosistemas (Aparicio et al 2009) que contribuyen a la protección de riberas, regulación del cauce de los ríos y retención de la sedimentación de las aguas. Por…”
Section: Introductionunclassified
“…Ello ha hecho necesario enfocar las investigaciones a aquellas especies que cumplen otras funciones como, por ejemplo, el soporte de ecosistemas (Aparicio et al 2009) que contribuyen a la protección de riberas, regulación del cauce de los ríos y retención de la sedimentación de las aguas. Por otro lado, se favorece también la nidificación y refugio de especies de fauna silvestre tales como Patagioenas araucana (Lesson) (torcaza) y Lontra provocax (Thomas) (huillín).…”
Section: Introductionunclassified
“…In macropropagation, various factors have been reported to influence the rooting of cuttings in tree crops out of which hormone concentrations and nodal position are the most important [7]. Tree species vary considerably in the optimal application of hormone and there is also much intraspecific variation [19]. This form of variation is not well understood in most of our indigenous tree species.…”
Section: Introductionmentioning
confidence: 99%